THE INFLUENCE OF WORK PERFORMANCE, MOTIVATION, AND JOB PLACEMENT SUITABILITY, TOWARDS WORK SATISFACTION (A STUDY TOWARDS STIE MALANGKUCECWARA / MALANG ECONOMICS ACADEMY PRIVATE HIGHER EDUCATION) - Tita Boedi Astuti (Unitri Press, 2017)
This research aims to find out the influence of performance, motivation, and job placement suitability towards work satisfaction for STIE Malangkucecwara Malang//Malang Economics Academy’s employee. This is quantitative research with explanatory research as research method. The samples are 56 persons from 56 persons population with saturated sampling technique. This research used multiple linear regression statistic analysis to test the proposed hypothesis. This research result proved three things: there is simultaneous influence from work assessment, motivation, and job placement suitability towards work satisfaction, there is partial influence from work satisfaction and job placement suitability towards work satisfaction, and work performance assessment is the main factor in influencing work satisfaction among the employees of STIE Malangkucecwara Malang. This means that work performance assessment, motivation, and job placement suitability are significantly able to improve STIE Malangkucecwara Malang’s employees’ work satisfaction.